2020
DOI: 10.1186/s12859-020-03573-8
|View full text |Cite
|
Sign up to set email alerts
|

PVAmpliconFinder: a workflow for the identification of human papillomaviruses from high-throughput amplicon sequencing

Abstract: Background: The detection of known human papillomaviruses (PVs) from targeted wet-lab approaches has traditionally used PCR-based methods coupled with Sanger sequencing. With the introduction of next-generation sequencing (NGS), these approaches can be revisited to integrate the sequencing power of NGS. Although computational tools have been developed for metagenomic approaches to search for known or novel viruses in NGS data, no appropriate tool is available for the classification and identification of novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…However, the classification of these PVs as animal types could be due to the limited information on the HPV L1 sequence, and the consideration of additional parts of the genome could result in a different classification as closely related HPVs. 19 In conclusion, using a well-validated NGS strategy, this study expanded our knowledge on HPV diversity in the anal mucosa. It showed that, besides infections with alpha HPVs, many beta and gamma HPV types from different species colonize the anal mucosal epithelium.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…However, the classification of these PVs as animal types could be due to the limited information on the HPV L1 sequence, and the consideration of additional parts of the genome could result in a different classification as closely related HPVs. 19 In conclusion, using a well-validated NGS strategy, this study expanded our knowledge on HPV diversity in the anal mucosa. It showed that, besides infections with alpha HPVs, many beta and gamma HPV types from different species colonize the anal mucosal epithelium.…”
Section: Discussionmentioning
confidence: 59%
“…17 , 18 Bioinformatic analysis was performed using the bioinformatic pipeline PVAmpliconFinder. 19 All the results in this study were based on the identification of the sequences following the homology-based classification using the evolutionary placement algorithm (EPA) in RAxML (Randomized Axelerated Maximum Likelihood). Only the longest sequence was considered for RAxML-EPA classification when several singlets or contigs were clustered together by PVAmpliconFinder.…”
Section: Ngs Broad-spectrum Analysis and Bioinformatic Analysismentioning
confidence: 99%
“…Alternatively, this result can also be explained by a lack of specificity of the amplification due to the use of degenerated primers. We also detected DNA sequences from several beta HPV types from species beta-1, beta-2 and beta-3 (HPV20, 23,24,49,93,98,124) and from gamma-1 (HPV205) (Tables 3, 4). Cutaneous beta HPV types, specifically beta-2 HPV111 (n = 3) and HPV120 (n = 1), were only detected by Luminex assay in DNA extracted from surrounding tissues.…”
Section: Discussionmentioning
confidence: 99%
“…NGS analysis was performed on the pooled amplicon-based library (Nextera DNA Flex) using the Illumina MiSeq sequencer (2 X 150 paired-end reads, MiSeq reagent kit v3) (Illumina, San Diego, CA, USA) as previously reported [21]. Bioinformatic analyses were performed using PVAmpliconFinder tool [23], and all the results were based on the homology-based classification using the evolutionary placement algorithm in RAxML (Randomized Axelerated Maximum Likelihood) [24].…”
Section: Library Preparation and Ngs Assaymentioning
confidence: 99%